Towards Esoteric Futures beyond the Apocalypse: Mystery and the Sacred in Climate Collapse and Technological Accelerationism - van Leeuwen, Gijs (Futures Reframed, 2026)
This essay problematizes monolithic futures characterized by an apocalyptic outlook and a scientific worldview, which constrain the scope of future possibilities. It does so by positioning the framework of esoteric futures, which serves to shows these monolithic tendencies as well as alternative pathways. This framework is based upon an alternative reading of Plato’s Allegory of the Cave, which complexifies the common utopian interpretation which revolves around a privileging of ‘light’ over ‘darkness’. Instead of focusing on Plato’s ideal – and potentially monolithic – state, this essay builds on the metaphors of the Cave to imagine the administration of the imperfect – and non-monolithic– state. It does so through two core concepts: mystery and the sacred. The framework is applied to two sets of prevalent present-day futures, climate collapse and technological accelerationism, to interpret monolithic tendencies and alternative pathways in both.